Wind Energy in the Mediterranean Spanish ARC: The Application of Gravity Based Solutions - Abanades, Javier (Frontiers in Energy Research, 2019)
Almost 90% of the world's marine renewable energy is generated in Europe, however the contribution of the Mediterranean Sea in the energy mix is practically negligible. On this sense, the present article presents the advantages of implementing a Blue Energy Project (offshore wind farm) in the Mediterranean Spanish Arc using certain type of technology: Gravi3®, a gravity based solution for the foundation of Wind Turbine Generators (WTGs). The analysis of the renewable energy potential and the boundary conditions of the case study analyzed (Cadiz) vindicates that the viability from both the technical and economic point of view can be assured.